Determinantes da composição corporal em crianças e adolescentes - Pérez, Lisiane Marçal (2018)
Introduction: The analysis of body composition is fundamental, since it is associated with the general health of individuals. Objective: To evaluate the association between socioeconomic and clinical variables with body composition in children and adolescents. Methods: Were included for convenience, participants between 5 and 19 years. Socioeconomic and clinical variables were assessed by a standardized questionnaire and corporal bioimpedance by Biospace, model InBodyS10, from Ottoboni. The variables studied were compared in relation to sex by t-test for independent and chi-square samples. The outcome variables (body mass index, skeletal mass, fat free mass and fat percentage )and predictor variables (age, sex, race, place of residence, father's schooling, physical activity, birth weight and breastfeeding )were analyzed using the quantile regression model (percentile 5, 50 and 95). The testes were bidirectional and were compared in comparison with p <0.05. Results: Among the 529 participants included, 284 (53.6%) were female and mean age was 11.41 ± 3.9 years. The body mass index was the only one to be dissociated from the majority of the sexes (p = 0.753). The decrease in weight was associated with lower skeletal muscle mass (Difference = -8.51, 95% CI -11.12 to -5.90, p <0.001), lower fat-free mass (Difference = -13.80, 95% CI (P <0.001) and lower body mass index (Difference = -2.88, 95% CI - 4.42 to - 1.33, p <0.001) when adjusted for birth weight and breastfeeding. The lowest percentage of fat was associated with an inexpensive relative (Difference = -5.01, 95% CI -9.45 to -0.56, p = 0.027) only in the crude analyzes. Conclusion: Muscle mass,fat free mass, skeletal muscle mass and body mass index are associated with family income.